Dengue viruses in Papua New Guinea: evidence of endemicity and phylogenetic variation, including the evolution of new genetic lineages - Peter R Moore; Andrew F van den Hurk; John S Mackenzie; Alyssa T Pyke (Emerging Microbes and Infections, 2017)
Dengue is the most common cause of mosquito-borne viral disease in humans, and is endemic in more than 100 tropical and subtropical countries. Periodic outbreaks of dengue have been reported in Papua New Guinea (PNG), but there is only limited knowledge of its endemicity and disease burden. To help elucidate the status of the dengue viruses (DENVs) in PNG, we performed envelope (E) gene sequencing of DENV serotypes 1–4 (DENV 1–4) obtained from infected patients who traveled to Australia or from patients diagnosed during local DENV transmission events between 2001 and 2016. Phylogenetic analysis and comparison with globally available DENV sequences revealed new endemic PNG lineages for DENV 1–3 which have emerged within the last decade. We also identified another possible PNG lineage for DENV-4 from 2016. The DENV-1 and 3 PNG lineages were most closely related to recent lineages circulating on Pacific island nations while the DENV-2 lineage and putative DENV-4 PNG lineage were most similar to Indonesian sequences. This study has demonstrated for the first time the co-circulation of DENV 1–4 strains in PNG and provided molecular evidence of endemic DENV transmission. Our results provide an important platform for improved surveillance and monitoring of DENVs in PNG and broaden the global understanding of DENV genetic diversity. Emerging Microbes & Infections (2017) 6, e114; doi:10.1038/emi.2017.103; published online 20 December 2017